Analisis Kesulitan Belajar Matematika Siswa Di Kelas VI SD Negeri 101944 Deli Muda - Hidayat, Nadya Agustina, (CV. PUSDIKRA MITRA JAYA, 2022)
Decreased student learning outcomes indicate the occurrence of difficulties in learning. This research was conducted to determine students' learning difficulties in mathematics in grade VI, the level of students' learning difficulties in mathematics, and to find out the causes of students' learning difficulties in mathematics in class VI SD Negeri 101944 Deli Muda. The research design is descriptive analysis, where this research uses quantitative research methods. the level of learning difficulties of students, especially in learning mathematics in class VI amounted to 63.1% which were identified as having learning difficulties in class, or in other words there were 12 out of 19 students / I who experienced learning difficulties with the type of learning difficulties in mathematics (Discalculia) which included difficulties in understand the concept of arithmetic in the material for addition of integers, mixed arithmetic operations, and understand how to solve problems in the material for solving area and perimeter problems in plane and geometric shapes. There is 5.2% at the level of difficulty with the type of reading difficulty or (dyslexia) or in other words there is 1 student who experiences an error when reading the questions. The level of difficulty with the type of writing learning difficulty (Disgraphia) is 0%, because there are no students in grade VI who have difficulty writing. There are several factors that cause learning difficulties in mathematics to occur, namely internal factors that occur from within the student, which include student interest and motivation in learning, study habits, and the health condition of the student's body. While external factors that occur from outside the student's self, which include environmental conditions, the relationship between teacher and student, and media/learning aids.